On the Possibility of Non-representational Cinema. From André Bazin to Gilles Deleuze - Brašiškis, Lukas (Religija ir kultūra, 2012)
Referring to the ontological arguments shown in the theory of the French film critic and theorist André Bazin and the arguments elaborated by Gilles Deleuze in the fourth chapter of his book Cinema 1: Movement-Image, the possibility of the cinema that does not duplicate the reductive tendencies of the intentional human consciousness is discussed in this article. The classical un-derstanding of the notion of cinematic realism is compared with the idea of non-representational cinema, accentuating the partially technological and partially subjective nature of film, which was described by Bazin, and its way to put the film viewer closer to the perception of the Bergso-nian acentric reality. Instead of giving a clear conclusion, the Bazinian idea of the non-anthropo-centric cinema is actualized in the light of the speculative turn in today’s philosophy.